2018
DOI: 10.1073/pnas.1811186116
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activation of glycosyl phosphates for stereoselective coupling reactions

Abstract: Glycosyl phosphates are shown to be activated to stereospecific nucleophilic substitution reactions by precisely tailored bis-thiourea catalysts. Enhanced reactivity and scope is observed with phosphate relative to chloride leaving groups. Stronger binding (Km) to the H-bond donor and enhanced reactivity of the complex (kcat) enables efficient catalysis with broad functional group compatibility under mild, neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 32 publications
0
42
0
1
Order By: Relevance
“…On the organocatalytic front [60][61][62][63][64] , seminal studies by Galan and McGarrigle et al demonstrated the utility of thiourea catalysis in accessing 2-deoxyglycosides via mild organocatalytic conditions 47,56 . However, significant limitations still exist in such protocols.…”
mentioning
confidence: 99%
“…On the organocatalytic front [60][61][62][63][64] , seminal studies by Galan and McGarrigle et al demonstrated the utility of thiourea catalysis in accessing 2-deoxyglycosides via mild organocatalytic conditions 47,56 . However, significant limitations still exist in such protocols.…”
mentioning
confidence: 99%
“…Computational studies suggested the coordination of the thiourea moieties to the chloride ion activates the donor, and the amide group on 21 concomitantly enhances the nucleophilicity of the acceptor in the transition state. Glycosylations of glycosyl phosphate, using a similar bis‐thiourea catalyst, have also been reported …”
Section: Organocatalysismentioning
confidence: 90%
“…[18] Jacobsen explained the electronic and steric influence of the Ar groups,the kinetics and solvent effects and the mechanistic insights obtained from different transformations. [19] Theg ained mechanistic understanding allowed the Jacobsen group to tackle challenging transformations like site-selective glycosidations [20] and to exploit the cooperative reactivity of H-bond donors and Lewis acids. [21] Tuesday 7thofM ay On Tuesday morning Jonathan Clayden (University of Bristol) gave an inspiring lecture about the biomimetic function from folded molecules.W eg ained deep insight in conformational challenges.H ed escribed how the conformational understanding can lead to the design and synthesis of molecular communication devices [22] with the capability to transfer information to remote reactive sites.Heenlightened the importance of foldamers [23] (conformationally defined molecules) ( Figure 4) towards their potential ability to mimic biological function.…”
Section: Sunday 5tho Fmaymentioning
confidence: 99%